Off-label use of intravenous rifampicin during surgery: analysis of Australian surveillance data and retrospective audit at a tertiary hospital - Nadine T. Hillock; Edward Raby; Matthew Rawlins (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract